The Relationship between Capital Structure and Market Power : Evidence from Nasdaq Helsinki - Sentiakov, Serguei (My University, 2019)
Firms’ actions in the product market and their capital structure decisions have traditionally been studied separately. In fact, industrial organization theories have largely ignored the link between capital structure and product market behavior and, similarly, financial economists have ignored the possibility of product market rivalry when examining firms’ optimal capital structure. Theories exploring the interaction between capital structure decision and product market characteristics have not emerged until the 1980’s. This study utilizes the recently developed theories in examining empirically public firms’ capital structure decisions. Two hypotheses regarding the relationship between firms’ market power and financial leverage are set forth in the study. Regression analysis is applied in order to test these hypotheses. The panel dataset used in the analysis contains the financial statement data of 58 firms listed on Nasdaq Helsinki in the time period 2002-2017. The following sectors are included in the analysis: basic materials, consumer goods, consumer services, industrials and technology. The regression analysis results support the hypothesis according to which a relationship between the sample firms’ financial leverage and market power is nonlinear. The study argues that the nonlinear relationship between the aforementioned variables may be explained by the combination of several theories that explore the interaction between firms’ capital structure decisions and their actions in the product market. These theories address, among other things, the predatory behavior of firms in the product market and the effects of debt on firms’ output strategies. The relationship between financial leverage and variables such as a firm’s profitability, size, growth and tangibility of a firm’s assets is also examined. The majority of the existing empirical research on the subject utilizes Tobin’s Q and various industry concentration measures as proxies for firms’ market power. By contrast, this study employs the average markup to measure market power.
Keywords: capital structure, market power, product market, competition, financing, leverage